Theorem znegeqd | index | src |

theorem znegeqd (_G: wff) (_n1 _n2: nat):
  $ _G -> _n1 = _n2 $ >
  $ _G -> -uZ _n1 = -uZ _n2 $;
StepHypRefExpression
1 hyp _nh
_G -> _n1 = _n2
2 1 zsndeqd
_G -> zsnd _n1 = zsnd _n2
3 1 zfsteqd
_G -> zfst _n1 = zfst _n2
4 2, 3 znsubeqd
_G -> zsnd _n1 -ZN zfst _n1 = zsnd _n2 -ZN zfst _n2
5 4 conv zneg
_G -> -uZ _n1 = -uZ _n2

Axiom use

axs_prop_calc (ax_1, ax_2, ax_3, ax_mp, itru), axs_pred_calc (ax_gen, ax_4, ax_5, ax_6, ax_7, ax_10, ax_11, ax_12), axs_set (elab, ax_8), axs_the (theid, the0), axs_peano (peano2, addeq, muleq)